2020
DOI: 10.1523/eneuro.0466-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Attentional Selection in Macaque Visual Cortex: Feature-Based Facilitation and Location-Based Inhibition of Return

Abstract: Visual search performance varies with stimulus and response history. Priming of pop-out refers to increased accuracy and reduced response time with repeated presentation of particular singleton and distractor features (e.g., a red target among green distractor stimuli), which are abruptly impaired when singleton and distractor features swap (e.g., green target among red distractors). Meanwhile, inhibition of return refers to slowing of response time when target location repeats. Neurophysiological correlates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 66 publications
1
41
2
Order By: Relevance
“…This mechanism is called Inhibition Of Return (IOR). Originally discovered in human studies of attention, inhibition of return is a tendency for the organism to orient away from a previously attended location and biologically depends on neural structures that participate in oculomotor control 29 , parietal and frontal cortex 37 . This phenomenon was first described by Posner and Cohen 38 who showed that reaction times to detect objects appearing in previously cued locations were longer than to uncued locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is called Inhibition Of Return (IOR). Originally discovered in human studies of attention, inhibition of return is a tendency for the organism to orient away from a previously attended location and biologically depends on neural structures that participate in oculomotor control 29 , parietal and frontal cortex 37 . This phenomenon was first described by Posner and Cohen 38 who showed that reaction times to detect objects appearing in previously cued locations were longer than to uncued locations.…”
Section: Resultsmentioning
confidence: 99%
“…In the proposed framework, the encoding of the oculomotor command needs a simple neuronal hardware, with the very mild assumption of units that perform sum operation, without the need of backward flows, leading to a plausible and straightforward biological implementation. The literature indicates that the V1 area is important for the conformation of the bottom-up saliency 27 , 28 , while other associative areas such as V4, FEF and supplementary eye field (SEF) 29 receive signals simultaneously from both the V1 area and deeper layers 30 . Neurons in the V1 area can encode principal and independent components extracted directly from the visual input 28 , and the response magnitude of such neurons is greater when the stimulus is distinct from its surrounding 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In target search, the comparison is between objects in the display and a target representation; in popout search, the comparison is between objects in the display and one another. In both cases, the representations depend on ventral-stream visual areas like V4 and IT (Zhou & Desimone, 2011;Westerberg, Maier, & Schall, 2020) as well as prefrontal areas (Bichot et al, 2015;Bichot, Xu, Ghadooshahy, Williams, & Desimone, 2019). The processing involved in popout is likely related to the identification-based feedforward inhibition we already identified as important for target selection.…”
Section: Extensionsmentioning
confidence: 89%
“…All procedures were in compliance with regulations set forth by the Association for the Assessment and Accreditation of Laboratory Animal Care (AALAC), approved by the Vanderbilt University Institutional Animal Care and Use Committee, and followed National Institutes of Health guidelines. A detailed description of the surgical procedures can be found in previous publications (Westerberg et al, 2019(Westerberg et al, , 2020a. Briefly, in a series of surgeries, each monkey was implanted with a custom MRI-compatible headholder and recording chamber over perifoveal V1 concurrent with a craniotomy.…”
Section: Animal Care and Surgical Proceduresmentioning
confidence: 99%
“…Channels in the gray matter were found by determining first whether a visual response could be evoked on the channel and second, whether a receptive field was present for the multiunit and/or LFP activity through a previously described receptive field mapping paradigm (Westerberg et al, 2019). If the channel was found to be in the gray matter, the broadband neural signal recorded at that channel was then band-pass filtered between 500 and 5,000 Hz, rectified, and low-pass filtered at 200 Hz using Butterworth filters (Self et al, 2013;Shapcott et al, 2016;Westerberg et al, 2020a). These derived neural signals, with no further filtering of the multiunit activity, were then used in performing both the univariate and multivariate analyses ( Figure 1D).…”
Section: Data Preprocessingmentioning
confidence: 99%